If you are solving for "h" here you go.
Simplifying
3(2 + -0.9h) + (-1.3h + -4) = 0
(2 * 3 + -0.9h * 3) + (-1.3h + -4) = 0
(6 + -2.7h) + (-1.3h + -4) = 0
Reorder the terms:
6 + -2.7h + (-4 + -1.3h) = 0
Remove parenthesis around (-4 + -1.3h)
6 + -2.7h + -4 + -1.3h = 0
Reorder the terms:
6 + -4 + -2.7h + -1.3h = 0
Combine like terms: 6 + -4 = 2
2 + -2.7h + -1.3h = 0
Combine like terms: -2.7h + -1.3h = -4h
2 + -4h = 0
Solving
2 + -4h = 0
Solving for variable 'h'.
Move all terms containing h to the left, all other terms to the right.
Add '-2' to each side of the equation.
2 + -2 + -4h = 0 + -2
Combine like terms: 2 + -2 = 0
0 + -4h = 0 + -2
-4h = 0 + -2
Combine like terms: 0 + -2 = -2
-4h = -2
Divide each side by '-4'.
h = 0.5
Simplifying
h = 0.5
You're welcome! C: